POLYGONAL IMPACT CRATERS IN THE ARGYRE REGION, MARS: EVIDENCE FOR INFLUENCE OF TARGET STRUCTURE ON THE FINAL CRATER MORPHOLOGY - Öhman T.; Aittola M.; Kostama V.-P.; Hyvärinen M.; Raitala J. (My University, 2006)
Impact craters that in plan view are distinctly polygonal rather than circular or elliptical are common on Mars and other planets (Öhman et al. 2005). Their actual formation mechanism, however, is somewhat debatable. We studied the polygonal craters of different degradational stages in the region of the Argyre impact basin, Mars. The results show that in the same areas, heavily degraded, moderately degraded, and fresh polygonal craters display statistically similar strike distributions of the straight rim segments. The fact that the strike distributions are not dependent on lighting conditions was verified by using two data sets (Viking and MOC-WA) having different illumination geometries but similar resolutions. In addition, there are no significant differences in the amount of polygonality of craters in different degradational stages. These results clearly imply that large-scale polygonality is not caused by degradation, but originates from the cratering process itself, concurring with the findings regarding lunar craters by Eppler et al. (1983). The straight rims of polygonal craters apparently reflect areal fracture patterns that prevail for a geologically long time. © The Meteoritical Society, 2006.